The electromagnetic interference shielding effect of indium-zinc oxide/silver alloy multilayered thin films - Kim, WM; Ku, DY; Lee, IK; Seo, YW; Cheong, BK; Lee, TS; Kim, IH; Lee, KS (ELSEVIER SCIENCE SA, 2005)
A study was made to examine the electromagnetic interference (EMI) shielding effect of multilayered thin films in which indium-zinc oxide (IZO) thin films and Ag or Ag alloy thin films were deposited alternately at room temperature using a RF magnetron sputtering. The optical, electrical and motphological properties of the constituent layers were analyzed using an ultraviolet-visible photospectrometer, a 4-point probe and an atomic force microscopy (AFM), respectively. The EMI shielding effect of the multilayered thin films was also measured using a coaxial transmission line method. A detailed analysis showed that the control of the film morphologies, i.e., the surface roughnesses of the constituent metal layers was essential to an accurate estimate of the electrical and optical properties of multilayered coatings. It was shown that properly designed IZO/Ag alloy multilayered thin films could yield a visible transmission of more than 70%, a sheet resistance of less than 1 Omega/sq., together with an EMI shielding effect larger than 45 dB in the range from 30 to 1000 MHz. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: LOW-RESISTANCE; DEPENDENCE